Measurement of in vivo therapeutic mAb concentrations: comparison of conventional serum/plasma collection and analysis to dried blood spot sampling. (August 2013) - Matsuda, Katherine C; Hall, Colin; Baker-Lee, Cassandra; Soto, Marcus; Scott, George; Prince, Peter J; Retter, Marc W
Background: Development of an alternative sampling method that uses small amounts of whole blood, such as dried blood spots (DBS), would be an advance in the quantitative assay field. Previously, we assessed the ability to quantitate therapeutic monoclonal antibodies present in DBS compared with a typical serum sample-based method, and concluded that measurements in DBS were reproducible and yielded methods that met requirements for precision, accuracy and sensitivity. The goal herein was to assess the measurement of therapeutic antibodies in DBS compared with serum and plasma in vivo .Results: Comparison of DBS versus serum in Sprague–Dawley rats and DBS versus plasma in cynomolgus monkeys for measurement of antibody concentrations revealed a two- to three-fold difference in exposure between the samples.Conclusion: Overall, there was good correlation between DBS versus serum and DBS versus plasma, but there was a discrepancy in DBS exposures, presumably attributable to hematocrit and recovery effects.